(untitled) (AYUSHDHARA, 2019)
Infertility is defined as the inability to conceive after 12 months of unprotected sexual intercourse. Though population of the world is increasing day by day yet 20-30% population of the world are the victims of the infertility and about 30-40% of cases men alone are contributory. Cause of infertility is being impaired sperm production or its functions, impaired sperm delivery, due to vicious life style and environmental exposure. According to Ayurveda absence or production of less quantity of semen is the main feature of Shukra kshaya and explains 8 pathological entities which damages normal composition of semen. Vajikarana is one of the specialised branches of Ashtanga Ayurveda dealing with Shukra dushti and Klaibya (semen disorders and sexual dysfunction) with management of Shukra dosha and Vandyatva. Although extensive research in fertility regulation has been elucidated, many of the secrets of reproductive health and the search for drug to modulate this natural phenomenon continues. Ayurveda has its own system of classifying the drugs based on their certain characteristics and actions they perform on the human body. The drugs which possess Madhura, Snigdha, Jivana, Brimhana, Guru properties are called Vrishya. Few examples are Amalaki, Kapikacchu, Shatavari, Shilajitu. So present paper highlights on conceptual aspect of Vrushya drugs in male infertility wsr to Shukra dosha. It includes male infertility according to Ayurveda and modern science, comparison between Shukra dosha with semen parameters and some of the Vrushya dravyas with its chemical constituents, specially, reactive oxygen species and its mode of action on infertility. All the relevant materials are compiled from the Ayurvedic texts and research articles.